2010
DOI: 10.1017/s1463423610000186
|View full text |Cite
|
Sign up to set email alerts
|

The stroke offspring study: is parental stroke history of value in targeted risk factor screening?

Abstract: This study aimed to compare the prevalence of stroke risk factors among people with a parental history of stroke to those in a control group of individuals, of similar age, gender and social class, with no parental stroke history. Background: Parental stroke increases an individual's risk of stroke, but little is known of the potential value of using this information in targeted screening for primary prevention in general practice. Method: We sent questionnaires to 300 randomly selected individuals aged 40-65 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…These findings suggest that individuals with a family history of stroke may not fully understand its significance, especially when combined with risk factors such as obesity, hypertension, and inadequate exercise. Similarly, Hart et al 36 found that persons with a parental history of stroke had significantly higher mean blood pressure readings than did those without a parental history, and they concluded that checking blood pressures in offspring of patients with stroke has potential value in identifying people likely to benefit from primary prevention. This finding differs from the findings of other studies that persons with a family history of disease had preventive health behaviors and intentions similar or superior to those without a family history.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that individuals with a family history of stroke may not fully understand its significance, especially when combined with risk factors such as obesity, hypertension, and inadequate exercise. Similarly, Hart et al 36 found that persons with a parental history of stroke had significantly higher mean blood pressure readings than did those without a parental history, and they concluded that checking blood pressures in offspring of patients with stroke has potential value in identifying people likely to benefit from primary prevention. This finding differs from the findings of other studies that persons with a family history of disease had preventive health behaviors and intentions similar or superior to those without a family history.…”
Section: Discussionmentioning
confidence: 99%